High Ectomycorrhizal Relative Abundance During Winter at the Treeline - Cubillos-Riffo, F; Oporto-Donoso, C; Villarreal-Diaz, P; Saona-Acuna, L; Urbina, K (Oxford University Press, 2025)
The rhizosphere is the soil region around plant roots hosting a diverse microbial community, influencing nutrient availability and how plants react to extreme conditions. However, our understanding of the fungi biodiversity and the impact of environmental variations on this biodiversity is still in its infancy. Our study investigates fungal communities diversity and functional traits in the rhizosphere of Nothofagus pumilio, one of the few winters deciduous treeline species in the world, forming the treeline in southern South America. At four distinct locations covering 10° latitude, we collected soil samples at treeline and 200 m below over four seasons during a single year. We employed ITS metabarcoding to elucidate fungal community structures. Our results reveal that fungal diversity was mainly determined by latitudinal variation, with higher levels during warmer seasons and lower altitudes. Interestingly, we found a marked dominance of ectomycorrhizal fungi at the treeline, particularly during the winter. In contrast, saprotrophic fungi were more abundant at lower altitudes, particularly during the warmer spring and summer seasons. These findings highlight the temporal and spatial dynamics of rhizospheric fungal communities and their potential roles in ecological processes, emphasizing the value of these communities as indicators of environmental change in high-elevation forests. © 2025 The Author(s).